The Influence Of Students' Learning Interest On Problem Solving Ability Using Diagnostic Assessment - Putri Salsabila, Nadia; Novika Sukmaningthias; Sari, Novita; Dwi Pratiwi, Weni (Universitas Islam Ahmad Dahlan (UIAD), 2024)
In Indonesia, the level of students' mathematical problem solving abilities can be said to be lacking due to the teacher's inability to condition a class well. So, to determine which method to use, teachers need to understand their students' abilities first, one of which is through diagnostic assessment. In this research, the researcher aims to find out whether it is possible that through diagnostic tests there is an influence on students' interest in learning on problem solving abilities in class VIII mathematics lessons at SMPN 46 Palembang. The type of research used is quantitative research with a sample of 29 students. The data collected used two techniques, namely questionnaires and also the results of diagnostic assessments. Meanwhile, the analysis used uses a technique which is a simple regression analysis test. Based on the results obtained, it shows that there is a high influence of interest in learning on the results of diagnostic assessments. The results obtained from the learning interest variable which influences the results of the diagnostic assessment in the form of problem solving abilities are results that can be said to be very high. In other words, it can be said that students' interest in learning greatly influences students' problem solving abilities as seen from the results of diagnostic assessments.